Knockdown of TMEM30A in renal tubular epithelial cells leads to reduced glucose absorption - Sipei Chen; Xinrou Song; Qiong Xiao; Li Wang; Xianjun Zhu; Yang Zou; Guisen Li (BMC Nephrology, 2023)
Abstract The kidney reabsorbs large amounts of glucose through Na+-glucose cotransporter 2 (SGLT2). P4-ATPase acts together with the β-subunit TMEM30A to mediate the asymmetric distribution of phosphatidylserine (PS), phosphatidylethanolamine (PE), and other amino phospholipids, promoting plasma membrane and internal vesicle fusion, and facilitating vesicle protein transport. We observed reduced TMEM30A expression in renal tubules of DKD and IgA patients, suggesting a potential role of TMEM30A in renal tubular cells. To investigate the role of TMEM30A in renal tubules, we constructed a TMEM30A knockdown cell model by transfecting mouse kidney tubular epithelium cells (TCMK-1) with TMEM30A shRNA. Knockdown of TMEM30A in TCMK-1 cells attenuated vesicle transporter protein synthesis, resulting in reduced transport and expression of SGLT2, which in turn reduced glucose absorption. These data suggested that TMEM30A plays a crucial role in renal tubules.